Do Nobel laureates change their patterns of collaboration following prize reception? - Ho Fai Chan; Ali Sina Önder; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2015)
We investigate whether Nobel laureates' collaborative activities undergo a negative change following prize reception by using publication records of 198 Nobel laureates and analyzing their coauthorship patterns before and after the Nobel Prize. The results overall indicate less collaboration with new coauthors post award than pre award. Nobel laureates are more loyal to collaborations that started before the Prize: looking at coauthorship drop-out rates, we find that these differ significantly between coauthorships that started before the Prize and coauthorships after the Prize. We also find that the greater the intensity of pre-award cooperation and the longer the period of pre-award collaboration, the higher the probability of staying in the coauthor network after the award, implying a higher loyalty to the Nobel laureate.
Keywords: 330; Nobel Prize; Nobel laureate; Award; Network; Coauthors; Recognition; Chemistry; Physics; Physiology or Medicine